COMMON SPEAKING ANXIETY PROBLEMS AMONG EFL LEARNERS - Izzatullaeva Yulduz Farmonovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Speaking anxiety is a well-documented issue that affects a significant proportion of English as a Foreign Language (EFL) learners worldwide. The challenge is rooted in a complex interplay between individual learner characteristics, the learning environment, pedagogical practices, social expectations, and the unique stresses of language acquisition. Despite the widespread prevalence of speaking anxiety among EFL learners, the underlying problems are often multifaceted and persistent, making effective communication in English a daunting task for many students.